2016
DOI: 10.1108/wje-08-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drying method of figs with small-scale flat-plate solar collector

Abstract: Purpose The purpose of the study was to develop a performance flat-plate solar collector that would be used as a solar drier for fruit fig (Ficus carica L). This study proposes how and why solar energy is important for drying the agricultural products. This study aims to expand the domain of solar collector for different purposes and, most important, for agricultural resource normally found in the literature. Design/methodology/approach The paper opted for an exploratory study using the flat-plate solar coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The samples were cut cylindrical tube with a length of 3.6 mm and a 1.4 mm in diameter and placed on the weighing balance. Ullah et al [21] reported that they are usually tiny and intense, growing 10-20 mm long and 3-7 mm in diameter. Asparagus samples were cut into cylindrical shapes with a length of 4mm, and a diameter of 6mm was also reported [22].…”
Section: Description Of the Experimental Proceduresmentioning
confidence: 99%
“…The samples were cut cylindrical tube with a length of 3.6 mm and a 1.4 mm in diameter and placed on the weighing balance. Ullah et al [21] reported that they are usually tiny and intense, growing 10-20 mm long and 3-7 mm in diameter. Asparagus samples were cut into cylindrical shapes with a length of 4mm, and a diameter of 6mm was also reported [22].…”
Section: Description Of the Experimental Proceduresmentioning
confidence: 99%
“…This thermal drying method is used as the main principle for many dryer types and has received wide attention in Effects of object shape and material the literature. Experimental and numerical studies were done for CD in different dryer types and combined as a supplementary process with other drying methods (Ullah et al, 2016;Kroehnke et al, 2018;Simo-Tagne et al, 2020;Bahammou et al, 2021;Ture and Chandramohan, 2021;Turgut et al, 2021), to investigate the complex structure of simultaneous coupled heat and mass transfers (HMTs) and other drying characteristics during processes. In recent years, numerical studies on HMT of porous bodies and food processing have taken an important place in literature because of their feasibility and lower costs than experimental studies, and with the rapid progress of computer programs and simulations, numerical studies have begun to obtain more accurate and precise results.…”
Section: Introductionmentioning
confidence: 99%